Graphene as a signal amplifier for preparation of ultrasensitive electrochemical biosensors - Filip, Jaroslav (Chem. Zvesti, 2014)
Early diagnostics of diseases performed with minimal money and time consumption has become achievable due to recent advances in development of biosensors. These devices use biorecognition elements for selective interaction with an analyte and signal readout is obtained via different types of transducers. Operational characteristics of biosensors have been reported to improve substantially, when a diverse range of nanomaterials was employed. This review presents construction of electrochemical biosensors based on graphene, atomically thin 2D carbon crystals, which is currently intensively studied nanomaterial. The most attractive directions of graphene applications in biosensor preparation are discussed here including novel detection and amplification schemes exploiting graphene’s unique electrochemical, physical and chemical properties. The future of graphene-based biosensors is most likely bright, but there is still a lot of work to do to fulfill high expectations.